2008
DOI: 10.1177/239700220802200205
|View full text |Cite
|
Sign up to set email alerts
|

Sociomoral Atmosphere and Prosocial and Democratic Value Orientations in Enterprises with Different Levels of Structurally Anchored Participation

Abstract: This study examines effects of structurally anchored organisational democracy on perceived sociomoral atmosphere and on employees' prosocial, democratic behavioural orientations. Data result from the ODEM research project. Beside a description of the concept of sociomoral atmosphere, within this project, 30 small and medium sized enterprises from Austria, North Italy, South Germany, and Liechtenstein (542 participants) were surveyed with questionnaires, interviews, and document analyses. Based on organisationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 30 publications
2
49
0
1
Order By: Relevance
“…In his 'just-community-approach' to moral development in schools, Kohlberg and colleagues stressed the role of a specific social school and classroom climatethe so called 'moral atmosphere' (Higgins 1995;Kohlberg 1985;Power et al 1989). The concept was adapted to the occupational domain by Lempert (1994) and was further developed into the construct of SMC by Weber et al 2008). SMC represents a sub-domain of the organizational climate referring to organizational practices of communication, teamwork, collective problem-solving and decision making, which follow rules of conduct based especially on Kantian ethics, Rawls' theory of justice, and the discourse-ethics by Habermas (see Pircher Verdorfer et al 2013a;Power et al 1989).…”
Section: Socio-moral Climate In Organizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In his 'just-community-approach' to moral development in schools, Kohlberg and colleagues stressed the role of a specific social school and classroom climatethe so called 'moral atmosphere' (Higgins 1995;Kohlberg 1985;Power et al 1989). The concept was adapted to the occupational domain by Lempert (1994) and was further developed into the construct of SMC by Weber et al 2008). SMC represents a sub-domain of the organizational climate referring to organizational practices of communication, teamwork, collective problem-solving and decision making, which follow rules of conduct based especially on Kantian ethics, Rawls' theory of justice, and the discourse-ethics by Habermas (see Pircher Verdorfer et al 2013a;Power et al 1989).…”
Section: Socio-moral Climate In Organizationsmentioning
confidence: 99%
“…SMC represents a sub-domain of the organizational climate referring to organizational practices of communication, teamwork, collective problem-solving and decision making, which follow rules of conduct based especially on Kantian ethics, Rawls' theory of justice, and the discourse-ethics by Habermas (see Pircher Verdorfer et al 2013a;Power et al 1989). Such a climate should form a field of socialization for moral orientations and competences (Power et al 1989;Weber et al 2008).…”
Section: Socio-moral Climate In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical foundation and practical operationalization are also based on Lempert's (1994) research on moral socialization in work places, wherein he identified a set of conditions that promote moral development. The socio-moral climate consists of the following six components (components 1 and 2 are thematically close and therefore combined in operationalization; Weber et al, 2008):…”
Section: Introductionmentioning
confidence: 99%
“…3 Weber et al 2008Weber et al , 2009Weber et al , 2011Weber et al , 2012Weber et al , 2013 Weber and its colleagues in their various studies provide empirical relationships between organizational democracy and other related variables.…”
mentioning
confidence: 99%